SYNTHESIZE AND CITOTOXICITYTEST OF SEVERAL COMPOUNDS OF MONO PARAHIDROXYCHALCON Sintesis dan UjiSitotoksisitas Beberapa Senyawa Mono Para-Hidroksi Kalko - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2009)
ABSTRACT Five compounds of mono para-hidroxy chalcon were synthesized (TC1, TC2, TC3, TC4, and TC5) and tested their cytotoxicity against HeLa cell and Raji cell. The difference in substituent of TC1 (R4=H), TC2 (R4= OCH3J,and TC3 (R4 = F), showed the difference of their citotoxicity against HeLa cell. The citotoxicity of TC1 (LC50= 16.08pg/mL)==TC3(LC50= 13.37pg/mL),but the substituentdifferenceof TC2(LC50= 147.43pg/mL), decreasing it citotoxicity 10 times. Like wise their citotoxicity against Raji cell of TC1 (LC50= 36.44 pg/mL) owTC3 (LC50= 30.46 pg/mL), but the substituent difference of TC2 (LC50= 468.94 ~g/mL), decreasing it citotoxicity activity 15 times. Nevertheless the strength of citotoxicity TC4 (LC50= '98.74pg/mL) and TC5 (LC50= 110.97pg/mL) against Raji cell are stronger than the citotoxicity of two of them against HeLa cell (LC50of TC4 = none, LC50of TC5 = 576.53 pg/mL). Keywords: mono para-hidroxy chalcon, HeLa cell, Raji cell, citotoxicity activity